We can evaluate two functions together if we apply the operations of mathematics.
Let f and g be the function.
Addition
f(x) = 2x^2 - 5x + 12
g(x) = 3x^2 + 7x -10
formula: (f + g) (x) = f(x) + g(x)
(f + g) (x) = 2x^2 - 5x + 12 + 3x^2 + 7x -10
(f + g) (x) = 5x^2 + 2x - 2
Subtraction
f(x) = 2x^2 - 5x + 12
g(x) = 3x^2 + 7x -10
formula: (f - g) (x) = f(x) + (-g(x))
(f + g) (x) = 2x^2 - 5x + 12 - (3x^2 + 7x -10)
(f + g) (x) = 2x^2 - 5x + 12 + (-3x^2 - 7x + 10)
(f + g) (x) = 2x^2 - 12x + 22
Multiplication f(x) = 2x + 5
g(x) = x^2 - 1
formula: (f x g) (x) = (f(x)) (g(x))
(f x g) (x) = (2x + 5) (x^2 - 1)
(f x g) (x) = 2x^3 - 2x + 5x^2 - 5
(f x g) (x) = 2x^3 + 5x^2 - 2x - 5
Division f(x) = 6x^2 - x -12
g(x) = 2x - 3
formula: (f/g) (x) = f(x)/g(x)
(f/g) (x) = 6x^2 - x -12/2x - 3
(f/g) (x) = (2x - 3) (3x + 4)/2x - 3
cancel 2x - 3 since there are both like terms
(f/g) (x) = 3x + 4
More References:
Addition:
![](https://static.wixstatic.com/media/5683a8_14de7fc1c07d451d80ddbd563ac0f1e5~mv2.jpg/v1/fill/w_980,h_735,al_c,q_85,usm_0.66_1.00_0.01,enc_auto/5683a8_14de7fc1c07d451d80ddbd563ac0f1e5~mv2.jpg)
Subtraction:
![](https://static.wixstatic.com/media/5683a8_9d8789a523f445188d08c81df5a4d98d~mv2.jpg/v1/fill/w_980,h_735,al_c,q_85,usm_0.66_1.00_0.01,enc_auto/5683a8_9d8789a523f445188d08c81df5a4d98d~mv2.jpg)
![](https://static.wixstatic.com/media/5683a8_a08fb114fc214c16b5d21bad9021a934~mv2.jpg/v1/fill/w_980,h_786,al_c,q_85,usm_0.66_1.00_0.01,enc_auto/5683a8_a08fb114fc214c16b5d21bad9021a934~mv2.jpg)
Multiplication:
![](https://static.wixstatic.com/media/5683a8_c07e3ee4df524902863a2cfda904feeb~mv2.jpg/v1/fill/w_980,h_735,al_c,q_85,usm_0.66_1.00_0.01,enc_auto/5683a8_c07e3ee4df524902863a2cfda904feeb~mv2.jpg)
Division:
![](https://static.wixstatic.com/media/5683a8_fc15fa864f514624b088a97a94110d97~mv2.jpg/v1/fill/w_980,h_735,al_c,q_85,usm_0.66_1.00_0.01,enc_auto/5683a8_fc15fa864f514624b088a97a94110d97~mv2.jpg)
Comentários